(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Andrianov T. V. Socio-pedagogical Problem of Healthy Lifestyle and Developmental Competence in Professional Activity. In the article the socialpedagogical problems of healthy way of life and development of personality competense are examined in relation to professional activity. The components of personality competence are given in relation to the question of healthy method lives, that are based on knowledge, experience, values, capabilities that is purchased due to physical culture and sport.